STATES FAILURE TO ANSWER TO CIVIL SOCIETY DEMANDS - Bijos, Leila (Unoesc International Legal Seminar, 2017)
On analyzing law and economics we consider that it is either embryonic or nonexistent in some developing countries as in Latin America. How to bring to the fore civil-law jurisdictions in particular, especially when it concerns to legal problems that range from the different structure of legal education, employment and cultural assets? This paper challenges this view by documenting and explaining the States failure to give answers to growing protests of the organized civil society in Brazil. Protests started with the inauguration of the Soccer Stadiums in 2013 and continued up to 2016. These movements have shaken up the political power which inertia is criticized by the young generation. The movement, also known as the Brazilian Spring, advocates for free public transportation, protest against increases in bus, train, and metro ticket prices in some Brazilian cities, but grew to include other issues such as high corruption on the government, in fact a crisis of representative democracy. Analytical emphasis is put on the contemporary Brazilian foreign policy, its political context, contemporary aspirations and the patterns of its engagement in several economic blocs, political alliances, the environmental protection of the Amazon, as well as questions concerned to employment, violence, defense and security.